Silent covenants : Brown v. Board of Education and the unfulfilled hopes for racial reform - Bell, Derrick, 1930-2011 (Oxford University Press, 2004)
Looks at continuing repercussions of Brown v. Board of Education and, despite the original intentions, its frequently negative impact on the educational needs of African-American children.